2016
DOI: 10.1186/s41065-016-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and occurrence of the F129L substitutions among isolates of Alternaria solani in south-eastern Sweden

Abstract: BackgroundEarly blight, caused by the fungus Alternaria solani, occurs on potato mainly in the south-eastern part of Sweden, but also in other parts of the country. The aim of this study was to investigate the genetic diversity of A. solani populations from different potato growing regions in south-eastern Sweden using AFLP marker analysis. In addition, the cultured isolates were examined for substitutions in the gene encoding cytochrome b, associated with loss of sensitivity against QoI fungicides.ResultsNei'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 31 publications
3
38
2
Order By: Relevance
“…It is hardly possible to identify tomato and potato germplasm with race-specific resistance since results of genetic studies on resistance to A. solani derived from different donors point to the same conclusion that resistance to the pathogen is expressed quantitatively that is controlled by minor genes (Chaerani et al 2007;Odilbekov 2015;Adhikari et al 2017). Averages of 8 plants × 3 replicates.…”
Section: Aggressiveness Testmentioning
confidence: 99%
See 4 more Smart Citations
“…It is hardly possible to identify tomato and potato germplasm with race-specific resistance since results of genetic studies on resistance to A. solani derived from different donors point to the same conclusion that resistance to the pathogen is expressed quantitatively that is controlled by minor genes (Chaerani et al 2007;Odilbekov 2015;Adhikari et al 2017). Averages of 8 plants × 3 replicates.…”
Section: Aggressiveness Testmentioning
confidence: 99%
“…Effectiveness of host resistance to A. solani is greatly influenced by the genetic variation of the pathogen (Odilbekov et al 2016). Previous studies revealed considerable variability among isolates with respect to morphology, physiology, biochemistry, aggressiveness and genetics (Bonde 1929;Henning and Alexander 1959;Petrunak and Christ 1992;Weir et al 1998;Castro et al 2000;Martinez et al 2004;van der Waals et al 2004;Varma et al 2006;Lourenço et al 2009;Lourenço Jr et al 2011;Weber and Halterman 2012;Meng et al 2015;Kumar et al 2016;Odilbekov et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations